What can be done about the private health sector in low-income countries? - Anne Mills; Ruairi Brugha; Kara Hanson; Barbara McPake (Bulletin of the World Health Organization)
A very large private health sector exists in low-income countries. It consists of a great variety of providers and is used by a wide cross-section of the population. There are substantial concerns about the quality of care given, especially at the more informal end of the range of providers. This is particularly true for diseases of public health importance such as tuberculosis, malaria, and sexually transmitted infections. How can the activities of the private sector in these countries be influenced so that they help to meet national health objectives? Although the evidence base is not good, there is a fair amount of information on the types of intervention that are most successful in directly influencing the behaviour of providers and on what might be the necessary conditions for success. There is much less evidence, however, of effective approaches to interventions on the demand side and policies that involve strengthening the purchasing and regulatory roles of governments.